EDUKASI GIZI MELALUI MEDIA BROSUR DAPAT MENINGKATKAN PENGETAHUAN SISWA SEKOLAH DASAR - Manjilala Manjilala; Hendayati Hendayati; Azkiannisa M (Media Gizi Pangan, 2023)
Nutrition education is very useful for increasing the nutritional knowledge of school children in building a positive attitude towards food as an effort to form good eating habits. The purpose of this study was to determine the effect of nutrition education using brochures on changes in knowledge about breakfast in elementary school children. This type of research is a one group pre and post test design at MI DDI Ujung Lare Parepare. The research sample took the entire population of all students in grades IV and V. Nutritional knowledge was collected by filling out questionnaires which were distributed directly. Statistical tests were carried out using the Wilcoxon test. The results showed that most of the class samples were in category IV 60%, gender was in the male category 57.5%, father's occupation was in the other category 32.5%, mother's work was in the PNS/TNI/Polri category 35%. The level of knowledge of the sample before being given education was in the category of good knowledge, 67.5%. An example of the level of knowledge after being given education with a good knowledge category is 100%. Statistical analysis using the Wilcoxon test showed that there was a difference in the score of nutritional knowledge before and after providing education through brochures about breakfast (p = 0.001). The media brochure acceptance rate of 82.5% really liked the brochure. Suggestions for further research are expected to use other media in accordance with technological developments so that it further supports the subject's interest in studying the information presented. This research needs to be studied further apart from measuring the level of knowledge, nutrition education should be carried out continuously and sustainably.